2017
DOI: 10.3390/molecules22122261
|View full text |Cite
|
Sign up to set email alerts
|

A DNA Barcode-Based RPA Assay (BAR-RPA) for Rapid Identification of the Dry Root of Ficus hirta (Wuzhimaotao)

Abstract: Background: Wuzhimaotao (the dry root of Ficus hirta) is used as both medicine and food ingredient by the locals in areas around Nanling Mountains of China. Due to its very similar external morphologies with Duanchangcao (the root of Gelsemium elegans, which contains gelsemine that is extremely neurotoxic) and the associated growth of these two plants, incidents of food poisoning and even death frequently occur, resulting from the misuse of Duanchangcao as Wuzhimaotao. The aim of this study is to develop a fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…However, several research groups have studied RPA reaction temperatures that lie outside of the recommended range. 38,44,45,60,[62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] The largest temperature range was tested between 15°C and 50°C; 62,64,69,70,76 and results indicated the marginal reaction temperature to produce a positive result should be greater than 30°C. [62][63][64]66,67,69,71,74,76,77 However, Sun et al 65 and Poulton and Webster 60 showed that temperature as low as 25°C could still generate a positive signal after RPA amplification and subsequent lateral flow strip detection.…”
Section: Influence Of Temperature and Agitationmentioning
confidence: 99%
“…However, several research groups have studied RPA reaction temperatures that lie outside of the recommended range. 38,44,45,60,[62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] The largest temperature range was tested between 15°C and 50°C; 62,64,69,70,76 and results indicated the marginal reaction temperature to produce a positive result should be greater than 30°C. [62][63][64]66,67,69,71,74,76,77 However, Sun et al 65 and Poulton and Webster 60 showed that temperature as low as 25°C could still generate a positive signal after RPA amplification and subsequent lateral flow strip detection.…”
Section: Influence Of Temperature and Agitationmentioning
confidence: 99%
“…Without the need for thermocyclers, this innovative approach can replace the traditional PCR technique’s unwinding chain process ( Piepenburg et al, 2006 ; Lobato and O’Sullivan, 2018 ). Tian et al (2017) developed a BAR-RPA assay to authenticate Traditional Chinese Medicine (TCM) products containing Wu Zhi Mao Tao, the roots of Ficus hirta Vahl. a valuable medicine and food ingredient found in China and effectively identified Gelsemium elegans (Gardner and Chapm.)…”
Section: Current Developments and Horizon Scanmentioning
confidence: 99%
“…The resulting RPA reaction products can be visualized in agarose gel electrophoresis, probe-based fluorescence monitoring, and lateral flow dipstick (LFD). In Tian et al (2017) reported a reliable protocol of DNA extraction and combine it with RPA-LFD to establish a rapid authentication of Ficus hirta from its adulterant, a toxic plant Gelsemium elegans. There are few reports that documented the use of the RPA technique for the identification of herbal medicines and their adulterants.…”
Section: Metabarcodingmentioning
confidence: 99%